Latin American Anthropological Philosophy: Ethnohistory and Archetype of the Decolonial Subject and its Pedagogical Practices - Gómez Romero, Danny Francis (Salud, Ciencia y Tecnología, 2022)
The aim of this article is to describe the philosophical, ontological, social bases of the Latin American context that served as support for the establishment of Lancasterian educational thought, based on scaffolding, cuts considered archetypal the present symbolic hermeneutical reflection that account for how It has been the process of pedagogical epistemological construction in Roman words "iuris tantum" that is to say, absolute presumption, in fact and in law (first in time and in law), what Latin history has registered and ours as well adopted it. The archetypal ethnohistorical hermeneutical method was used as a category of analysis: mentality, proposed by C. G. Jung for the interpretation of data, sources, texts, magazines, manuscripts, other official documents served as support to establish foundations and reflections. It is concluded in harmony with the author Cassirer, a reflection of philosophical anthropology that focuses on the concept of man as an symbolicum